Endothelial microparticles mediate inflammation‐induced vascular calcification. Issue 1 (23rd October 2014) - Buendía, Paula; de Oca, Addy Montes; Madueño, Juan Antonio; Merino, Ana; Martín‐Malo, Alejandro; Aljama, Pedro; Ramírez, Rafael; Rodríguez, Mariano; Carracedo, Julia
Abstract : Stimulation of endothelial cells (ECs) with TNF‐α causes an increase in the expression of bone morphogenetic protein‐2 (BMP‐2) and the production of endothelial microparticles (EMPs). BMP‐2 is known to produce osteogenic differentiation of vascular smooth muscle cells (VSMCs). It was found that EMPs from TNF‐α‐stimulated endothelial cells (HUVECs) contained a significant amount of BMP‐2 and were able to enhance VSMC osteogenesis and calcification. Calcium content was greater in VSMCs exposed to EMPs from TNF‐α‐treated HUVECs than EMPs from nontreated HUVECs (3.56 ± 0.57 vs. 1.48 ± 0.56 μg/mg protein; P < 0.05). The increase in calcification was accompanied by up‐regulation of Cbfa1 (osteogenic transcription factor) and down‐regulation of SM22α (VSMC lineage marker). Inhibition of BMP‐2 by small interfering RNA reduced the VSMC calcification induced by EMPs from TNF‐α‐treated HUVECs. Similar osteogenic capability was observed in EMPs from both patients with chronic kidney disease and senescent cells, which also presented a high level of BMP‐2 expression. Labeling of EMPs with CellTracker shows that EMPs are phagocytized by VSMCs under all conditions (with or without high phosphate, control, and EMPs from TNF‐α‐treated HUVECs). Our data suggest that EC damage results in the release of EMPs with a high content of calcium and BMP‐2 that are able to induce calcification and osteogenic differentiation of VSMCs.—Buendía, P., Montes de Oca, A., Madueño, J. A., Merino, A., Martín‐Malo, A., Aljama, P., Ramírez, R., Rodríguez, M., Carracedo, J., Endothelial microparticles mediate inflammation‐induced vascular calcification. FASEB J. 29, 173–181 (2015). www.fasebj.org